Analysis of Construction Material Waste in Hospital Building Projects Using Pareto and Fishbone Approaches - Grace Yoyce Malingkas; Muhammad Ihsan Jasin; Jessen Granbey Potalangi (Universitas Islam Raden Rahmat, Malang, 2026)
Material is one of the most important components in construction projects because it serves as the primary element of building structures and significantly influences project costs. Ineffective material management can result in construction material waste, leading to increased costs and reduced resource efficiency. This study aims to identify the dominant waste-generating materials and analyze the factors causing material waste in the Hermana Lembean General Hospital construction project. Data were collected from as-built drawings, material logistics reports, and field interviews. The Pareto method was used to determine the dominant waste materials, while the Fishbone Diagram method was applied to identify the root causes of material waste. The results showed that the total construction material waste generated during the project was 3,951.784 units. Pareto analysis indicated that reinforcing steel (53.21%), wall ceramic 60 × 60 cm (11.38%), lightweight brick (8.49%), and floor ceramic 60 × 60 cm (7.49%) were the dominant waste materials, accounting for more than 80% of the total waste volume. Fishbone Diagram analysis revealed that material waste was mainly caused by machine, method, material, manpower, and measurement factors. These findings can be used to improve material management and reduce waste in future construction projects.